Progress in Power Ultrasound Effect on Molten Metal Shaping and Its Visualization - LI Hong; LI Can; LI Zhuo-xin (Cailiao gongcheng, 2017)
The effect of power ultrasound in molten metal shaping was summarized. The application and mechanism of ultrasonic treatment in the grain refinement, degassing and impurity removal in casting process, as well as strengthening of weld seam by reducing residual stress and promoting interfacial wetting in welding process were reviewed in details. The progress in high-speed photography of ultrasonic cavitation bubbles and synchrotron radiation X-ray imaging of crystal growth in molten metal was reviewed and discussed. It was proposed to adopt in-situ investigation of mechanism of ultrasound in liquid metal medium by combining high-speed photography and synchrotron radiation X-ray imaging. It aims to provide theoretical guidance for further applications of ultrasound in the molten metal shaping.